2023
DOI: 10.1038/s41598-023-34834-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal social isolation on adult rodent offspring cognition

Robert J. McDonald,
Nancy S. Hong,
Jan S. Trow
et al.

Abstract: Prenatal experiences can influence offspring physiology and behaviour through the lifespan. Various forms of prenatal stress impair adult learning and memory function and can lead to increased occurrence of anxiety and depression. Clinical work suggests that prenatal stress and maternal depression lead to similar outcomes in children and adolescents, however the long-term effects of maternal depression are less established, particularly in well controlled animal models. Social isolation is common in depressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…The effect size of paternal isolation on offspring survival was moderate and biologically meaningful, with offspring captured, on average, over three times faster when their father was isolated compared to when he had a neighbor. These maladaptive effects are consistent with a previous study in rats, where offspring of socially-isolated mothers showed cognitive impairments and increased anxiety-like behaviors (McDonald et al . 2023).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The effect size of paternal isolation on offspring survival was moderate and biologically meaningful, with offspring captured, on average, over three times faster when their father was isolated compared to when he had a neighbor. These maladaptive effects are consistent with a previous study in rats, where offspring of socially-isolated mothers showed cognitive impairments and increased anxiety-like behaviors (McDonald et al . 2023).…”
Section: Discussionsupporting
confidence: 93%
“…Here, we demonstrate that social isolation in adult males does not just affect individuals within a lifetime, but also has detrimental consequences for offspring, leading to lower survival against a predator. This may arise because ancestral stress can make offspring more vulnerable to stress by reprograming the HPA axis, hampering offspring ability to respond appropriately to stress encountered within their own lifetime (Yehuda et al 2008;Rodgers et al 2013;Faraji et al 2017;McDonald et al 2023). Although no studies (to our knowledge) have looked at the transgenerational consequences of paternal isolation prior to fertilization, our results are consistent with previous studies demonstrating that other forms of paternal social stress, including maternal separation early in life (Gapp et al 2014), social defeat (Dietz et al 2011), and social instability (Kong et al 2021), alter offspring anxiety and corticosterone levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations